EARLY DIAGNOSTICS AND PERSONALITY COGNITIVE DEVELOPMENT CORRELATION AS THE FACTORS OF THE EFFICIENCY OF TEACHING (Scientific journal of the Fergana State University, 2023)
The article considers the problem of cognitive development of preschool children as a result of the action of a number of factors of an objective and subjective nature and the need for its early diagnosis and correlation as a condition for the effectiveness of learning and the success of personality development.